Understandings, pedagogical assumptions and experiences of permanent education in health in the state of Paraná-Brazil (Revista Contexto & Saúde, 2025)
Permanent education suggests the continuous acquisition of knowledge in the professionals' work context and based on their previous knowledge. This study aims to explore how permanent health education (PHE) has been integrated in the State of Paraná, from the point of view of professionals who work in regional health departments. This is a descriptive study with a qualitative approach, in which 23 professionals involved with EPS participated, the interviews were conducted online from July to September 2021. The interviews were submitted to thematic content analysis, emerging the themes: About the understanding of what permanent health education is; The pedagogical assumptions of permanent education in health; The experiences lived with UNA-SUS and PROADI-SUS; Obstacles faced to carry out permanent education in health. It is concluded that the experience of professionals working with EPS in the state takes plac e on two fronts, one being a distance education experience, which has a study environment on the UNA-SUS platform, in which professionals seek qualifications in several areas, and the other that focuses on the actions developed by the Escola de Saúde Pública do Paraná, together with the regional health departments and municipalities, and that there are challenges to be overcome for the affirmation of this policy in the state.
Keywords: Health education; permanent health education; lifelong learning; problem-based learning